Once‐daily rabeprazole, levofloxacin, clarithromycin‐MR, and bismuth for Helicobacter pylori eradication: A randomized study of 7 or 14 days (ONCE study). Issue 5 (7th July 2019) - Auttajaroon, Jeerayuth; Vilaichone, Ratha‐korn; Chotivitayatarakorn, Peranart; Mahachai, Varocha
Abstract: Objective: Most therapies for Helicobacter pylori eradication utilize multiple drugs given 2‐4 times daily. Patient adherence has been an impediment to reliably achieving high success. This study evaluated a once‐daily dosing H pylori eradication regimen. Methods: A prospective randomized pilot study of H pylori eradication compared once‐daily treatment regimen containing levofloxacin (750 mg), clarithromycin‐MR (1 g), rabeprazole (60 mg), and bismuth subsalicylate (1, 048 mg) for a 7 or 14 days. CYP2C19 genotype and antibiotic susceptibility tests were performed. Successful eradication was defined as negative 13C‐urea breath test at least 4 weeks after completion of treatment. Results: 100 subjects were randomized (40 men, 60 women with mean age =54 years). The eradication rates were as follows: 94% (47/50; 95%CI 0.87‐1.01) and 84% (42/50; 95%CI 0.73‐0.95) with 14‐day and 7‐day therapy (OR 0.34; 95%CI 0.08‐1.35, P  = 0.06), respectively. Resistance rates were as follows: 13.0% for clarithromycin, 26.0% for fluoroquinolone, 2.9% for dual clarithromycin‐fluoroquinolone resistance, and 62.8% for metronidazole. The 14‐day regimen provided 100% eradication in patients with levofloxacin susceptible strain irrespective of the presence of clarithromycin resistance. CYP2C19 genotypes had no effect on cure rates. Conclusions: The once‐daily 14‐day rabeprazole‐, levofloxacin‐, clarithromycin‐MR‐, and bismuth‐containing therapy provided high eradication rate suggested that triple therapies with a PPI, bismuth, and clarithromycin‐MR or levofloxacin would be highly effective for once‐a‐day tailored therapy or as empiric therapy for first‐line regimen.